2022
DOI: 10.1177/23821205221076659
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Resident Adherence to Evidence-Based Practices in Management of Diabetes Mellitus

Abstract: Objective Diabetic preventative health maintenance involves (1) adherence to guidelines and (2) appropriate documentation. This study evaluates the frequency with which internal medicine (IM) residents met these two outcomes. We also evaluated if there were differences in outcomes between resident classes. Methods In this retrospective analysis, 234 diabetic outpatient visits were analyzed. Guidelines were derived from the American Diabetes Association (ADA). The outcomes for each guideline were averaged and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our data also showed that regardless of ownership, laboratory tests such as hemoglobin A1C and serum creatinine were offered more frequently than others, such as foot exams, similar to what was found in previous studies. 7 , 8 This could be due to the relative ease of completing said services. Ordering a lab test may seem to be simpler than completing a comprehensive foot examination, and in a setting where time constraints are frequent, the latter could be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data also showed that regardless of ownership, laboratory tests such as hemoglobin A1C and serum creatinine were offered more frequently than others, such as foot exams, similar to what was found in previous studies. 7 , 8 This could be due to the relative ease of completing said services. Ordering a lab test may seem to be simpler than completing a comprehensive foot examination, and in a setting where time constraints are frequent, the latter could be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, physician adherence to these guidelines is poor, 5 , 6 with certain services, such as hemoglobin A1C testing, offered more frequently than others, such as foot exams. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%